Studi Perbedaan Karakter Disiplin Anak Kelompok B Berdasarkan Disiplin kerja Guru Di PAUD Kampung Bali Kota Bengkulu - Siyyella Tika Nasution; Nina Kurniah; Melia Eka Daryanti (Jurnal Ilmiah POTENSIA, 2017)
The research focuses on differences case of discipline character of early age students based on teacher’s performance disciplines at PAUD Kampung Bali Bengkulu City. The purpose of this research is to describe differences of discipline character of early age students of group B based on teacher’s performance disciplines. Method that was used is descriptive quantitative with comparative kind. Subject of this research is 40 children who consist of 13 children of Group B1, 13 children of Group B2, and 14 children of Group B3. Technique of collecting the data used statistics analysis with varian analysis one way formula. Results of this research were teacher’s performance disciplines at PAUD Kampung Bali was very good category and there is no difference between discipline character of early age students of Group B1, B2, and B3. Based on teacher’s performance discipline at PAUD Kampung Bali Bengkulu city was seen from Fcount value was 0,499 smaller than Ftable value which was  4,11 for 5% significant level (0,499<4,11). Suggestion in this research for teachers in investing good character into early age students should begin with teachers whose good character also.